Les cartes numériques de l'inventaire forestier national - Didon E. (Les incendies de forêt en région méditerranéenne : constitution et utilisation des bases de données, 1995)
The national forest inventory (IFN) has made a statistical inventory of French forest resources since 1960. The data gathered continuously feed a dendrometric database that can be used in particular to appraise the areas and increased volumes of forest stands and to simulate future change. The IFN presents the results in the form of departmental forestry monographs, forest atlases and departmental forest maps at 1:200,000. These are complemented today by the cartographic computer files used to incorporate the IFN data in computerised tools for spatial analysis.
Séminaire sur les Incendies de Forêt en Région Méditerranéenne, 1993/11/30-1993/12/04, Montpellier (France)